Nordycki Bank Inwestycyjny - Drzewicki, Krzysztof (Wydział Prawa i Administracji UAM, 1984)
The aim of the article is an attempt to analyse background, structure and activities of the Nordic Investment Bank and moreover, but subsidiarily, to survey its specific features in comparison with other similar financial organizations of the regional intergovernmental co-operation. Taking into account that the Bank was established as a specialized institution of the global Scandinavian system of co-operation, it seemed necessary motu proprio to define its position inside this system, with special attention to the extent and character of its links with both principal organizations of the Scandinavian co-operation, namely with the Nordic Council and Nordic Council of Ministers. This is particularly important because they both took part actively in the process of establishing the Bank and thus were in a position to reserve for themselves some influence on directions of its activities. The origins of the Bank were presented against a broader background of Scandinavian ventures in economic integration. The idea of the Nordic Investment Bank, in a form of relatively ripe conception, was already considered in the common market plans in 1957 and 1969. In both cases there was a general consent of experts as regards detailed organizational and functional provisions of the drafts, however they failed on the level of top political and economic negotiations. The third and, this time, successful attempt to set up the Bank took place in 1975. The structure of the Bank proves to be adequate to its tasks. According to the Statutes of the Bank, its activities during 1976 - 1982 demonstrate the preference to provide financing on normal banking terms of projects and exports beneficial to the Nordic region. Besides typical solutions applied in similar regional investment banks, the Nordic one distinguishes with some specific features. One of its exceptional features is no doubt a set of diversified forms linking the Bank not merely with regional intergovernmental body (Nordic Council of Ministers) but first of all with Scandinavian parliamentary-governmental assembly (Nordic Council). The operations of the Bank contribute essentially to stimulation and growth of Nordic economic interdependences and thereby diminishing to some extent the negative consequences of centrifugal tendencies in the region. It seems justified to conclude that the Nordic Investment Bank as the specialized institution has been thus flexibly connected with general directions of regional programme of Scandinavian co-operation and integration.
The Nordic Investment Bank